A Real Options Approach to Valuate Solar Energy Investment with Public Authority Incentives: The Italian Case - Antonio Di Bari (Energies, 2020)
Solar energy investment represents currently a valid reason to support sustainable economic development. In fact, over the last few years, governments have applied different measures to incentivize private consumers and firms to use renewable energies. Photovoltaic (PV) projects are characterized by uncertainty due to meteorological conditions, the unpredictable behavior of government, and managerial flexibility. Since the Net Present Value (NPV) approach is not able to capture these uncertain factors, it was replaced with the Real Options Approach (ROA). The latter method manages to embed flexibility in PV investment using binomial trees. This paper valuates PV investment in all regional areas in Italy using an integrated approach between the discounted cash flows method and real option value, called Expanded Net Present Value (ENPV). We fit the probability of tax benefits into a binomial lattice model after analyzing the geographical position and weather conditions of all regional capitals of Italy. The results show that the cities with high irradiance/temperature have positive NPV and high investment values. On the other hand, while most cities have negative NPV, the inclusion of the flexibility in investment decisions gives additional value to the project, making the ENPV positive and implying an attractive investment opportunity with the possibility of delaying the project. We also propose a sensitivity analysis that shows how the real option value changes when incentive policies of the government become more attractive. This paper contributes to the existing literature in the way of considering financial, meteorological/geographical, and political factors to valuate PV investment.